2011
DOI: 10.1111/j.1601-5037.2010.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of cigarette smoking effect on periodontal pocketing and attachment loss: a retrospective study

Abstract: Lack of interaction between smoking and any of the three position variables indicates that the destructive effects of smoking on the periodontal tissues maybe mainly from systemic side-effects and almost independent of the site position within the mouth, although some additional local effects may be present in areas such as anterior palatal sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…With the effect of CS on epithelial structure, smokers may thus be more at risk of periodontal dysfunction, leading to deep periodontium pocket formation . These pockets facilitate the accumulation of microbes, which, in turn, causes severe periodontitis owing to activation of the inflammatory pathways . Moreover, epithelial hyperplasia observed in smokers may be the result of cell proliferation and the modulation of multiple keratin markers .…”
mentioning
confidence: 99%
“…With the effect of CS on epithelial structure, smokers may thus be more at risk of periodontal dysfunction, leading to deep periodontium pocket formation . These pockets facilitate the accumulation of microbes, which, in turn, causes severe periodontitis owing to activation of the inflammatory pathways . Moreover, epithelial hyperplasia observed in smokers may be the result of cell proliferation and the modulation of multiple keratin markers .…”
mentioning
confidence: 99%
“…In several studies, smokers showed greater PD than non-smokers 25 , or had greater CAL, increased bone loss, deeper periodontal pockets, than nonsmokers 8,25 . There was no statistically significant difference in most clinical parameters evaluated, or in the levels of LL-37 and hBD-2 between smoking and nonsmoking patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine is a highly addictive chemical substance present in tobacco and causes nicotine dependence which makes quitting smoking, is very difficult being the major obstacle in smoking cessation programs. It is rapidly absorbed via the oral mucosa and the lung alveoli in such quantities producing its pharmacological effects [6]. On regular smoking, the nicotine binds in the brain to nicotinic cholinergic receptors and opens ion channels for sodium and calcium; elevated intracellular calcium concentration stimulates the release of neurotransmitters including dopamine which is responsible for the pleasant experience and promotion of the re-administration behaviour [7].…”
Section: Introductionmentioning
confidence: 99%